Inhibition of miR-185-3p Confers Erlotinib Resistance Through Upregulation of PFKL/MET in Lung Cancers - Li, Ke; Zhu, Xinling; Yuan, Conghu (Frontiers in Cell and Developmental Biology, 2021)
Erlotinib (ER), as an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), has significant therapeutic effect in lung cancers. However, EGFR-TKI resistance inevitably occurs after treatment for approximately 12 months, which weakens its anti-tumor effect. Here, we identified miR-185-3p as a significantly down-regulated miRNA responsible for acquired EGFR-TKI resistance in cells and patients with lung cancer. QRT-PCR and Western Blot were performed to determine the relative expression of miR-185-3p in ER-resistant tumor tissues and cells. The viability and apoptosis of lung cancer cells were evaluated by CCK8 assay and flow cytometry, respectively. The binding between miR-185-3p and PFKL was verified by dual luciferase assay. It was found that overexpression of miR-185-3p conferred ER-sensitivity in lung cancer cell lines. MiR-185-3p was down-regulated in ER-resistant lung cancer cells (H1299/ER and A549/ER). MiR-185-3p inhibited proliferation and induced cell apoptosis in ER-resistant cells. Mechanistically, miR-185-3p down-regulation contributed to ER resistance through up-regulating the liver-type phosphofructokinase (PFKL). Moreover, MET oncoprotein promoted EGFR TKI resistance by regulating miR-185-3p and PFKL. These findings revealed a novel mechanism in which down-regulation of miR-185-3p may induce overexpression of PFKL and MET, and confer the ER resistance in lung cells. Combination of PFKL/MET inhibitors and EGFR-TKIs could be a rational therapeutic approach for lung cancer patients with EGFR-mutation.